A bridge too far: dispersal barriers and cryptic speciation in an Arabian Peninsula grouper (Cephalopholis hemistiktos). (12th December 2015) - Priest, Mark A.; DiBattista, Joseph D.; McIlwain, Jennifer L.; Taylor, Brett M.; Hussey, Nigel E.; Berumen, Michael L.
Abstract: Aim: We use genetic and age‐based analyses to assess the evidence for a biogeographical barrier to larval dispersal in the yellowfin hind, Cephalopholis hemistiktos, a commercially important species found across the Arabian Peninsula. Location: Red Sea, Gulf of Aden, Gulf of Oman and Arabian Gulf. Methods: Mitochondrial DNA cytochrome‐ c oxidase subunit‐I and nuclear DNA ( S7 ) sequences were obtained for C. hemistiktos sampled throughout its distributional range. Phylogeographical and population‐level analyses were used to assess patterns of genetic structure and to identify barriers to dispersal. Concurrently, age‐based demographic analyses using otoliths determined differences in growth and longevity between regions. Results: Our analyses revealed significant genetic structure congruent with growth parameter differences observed across sampling sites, suggesting cryptic speciation between populations in the Red Sea and Gulf of Aden versus the Gulf of Oman and Arabian Gulf. Coalescence analyses indicated these two regions have been isolated for > 800, 000 years. Main conclusions: Our results indicate historical disruption to gene flow and a contemporary dispersal barrier in the Arabian Sea, which C. hemistiktos larvae are unable to effectively traverse. This provides yet another example of a (cryptic) species with high dispersive potential whose range is delimited by a lack of suitable habitat between locations or an inability to successfully recruit at the range edge.